Prospects of Entrepreneurial Competencies of Micro and Small Enterprise in Jimma Zone, Ethiopia (Global Journal of Management and Business Research, 2016)
Objective: The Objective of this Study is to assess the entrepreneurial competencies of Micro and Small enterprises of Jimma Zone. Methods: An enterprise based cross sectional study was done using both quantitative and qualitative methods in three purposively selected districts/towns of Jimma Zones namely Agaro, Limu Kossa, and Shebe Sombo. A total of 183 entrepreneurs from both Micro and small enterprises were randomly sampled for quantitative and 16 FGDs and 9 Key informant interviews were conducted to describe and determine the outcome of interest. The data were analyzed using SPSS 20 and qualitative data was managed by transcribing verbatim on daily basis. Results: All of the respondents were aged 19 years and above with mean age of 26.8±4.2. 71% of them were male managers indicating gender inequality in business leadership of micro and small enterprises of the zone. Majority 124(67.8%) of them were from families having no business. the result of this study indicates that there is high gender gap in the leadership of micro and small enterprises.
Keywords: describe and determine the outcome of interest